Data-driven services in insurance: Potential evolution and impact in the Swiss market - Carlo Pugnetti; Mischa Seitz (Journal of Risk and Financial Management, 2021)
Using real-time customer data holds great potential for the insurance industry. The frequency and relevance of interactions can be improved to provide assistance in real time. Better prevention and risk management can significantly improve pricing and reduce losses. These changes, however, hold the potential for structural changes in the industry. This research aims at understanding the potential path of the development of services in insurance and the challenges faced by insurers. A panel of industry experts provided the industry's view, which was then compared with the responses of 1542 Swiss retail customers. We find that customers have high trust in insurance companies and are open to purchasing additional services, particularly for prevention and assistance. Insurance companies, however, are currently focusing on cost improvement measures. Customers are open to sourcing services from other providers, suggesting that insurance companies need to evolve their approach to take advantage of the current market window.
Keywords: 330; customer behavior; insurance; services; technology